2021
DOI: 10.3390/biom11121818
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Low-Molecular-Weight Aβ42 Detection System Using a Enzyme-Linked Peptide Assay

Abstract: Alzheimer’s disease (AD) is a degenerative brain disease that is the most common cause of dementia. The incidence of AD is rapidly rising because of the aging of the world population. Because AD is presently incurable, early diagnosis is very important. The disease is characterized by pathological changes such as deposition of senile plaques and decreased concentration of the amyloid-beta 42 (Aβ42) peptide in the cerebrospinal fluid (CSF). The concentration of Aβ42 in the CSF is a well-studied AD biomarker. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Our journey in the report of the most recent application of CADD in peptide-based radiotracers starts with a contemporary application of the molecular docking analyses performed by Kim et al [ 20 ]. In this study, in silico investigation has been used to identify the overproduction of a specific protein responsible for Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Our journey in the report of the most recent application of CADD in peptide-based radiotracers starts with a contemporary application of the molecular docking analyses performed by Kim et al [ 20 ]. In this study, in silico investigation has been used to identify the overproduction of a specific protein responsible for Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although these biomolecules offered selective binding affinity with Aβ, disadvantages such as the stability of these biomolecules and the influence of steric hindrance along with tedious storage conditions limit their application. 30,31 Since Aβ contains a cascade of chirality and any change in the chiral environment either through variation in amino acids or through variation in isomerization and epimerization can lead to protein aggregation. Some recent reports have suggested that any change in d -Asp23 caused Aβ 42 (42 residues long) formation of β-lamellar fibers; similarly, d -serine levels were higher in the cerebrospinal fluid of AD patients, thus exploring that chirality-mediated strategies can become very promising for the inhibition of protein fibrils through “chiral–chiral” interactions between proteins and chiral nanomaterials via hydrophobic interaction, electrostatic interaction, and hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the accurate monitoring of Aβ42 is essential for the early diagnosis of AD. Several methods for the detection of Aβ42 have been reported, such as enzyme-linked immunoassay (EILSA), electrochemistry (EC), photochemistry, multiplex biosensors, and electrochemiluminescence (ECL) . Compared to most methods, ECL has a high sensitivity, simple devices, and excellent controllability.…”
Section: Introductionmentioning
confidence: 99%